Outstanding Bussiness english - Fiona Talbot (Diccionarios LID, 2016)
" ""Outstanding Business English gives guidance to non-native English speakers on how to communicate clearly and concisely. With case studies and real-life examples that demonstrate how English is used internationally in business, and full of ideas to help you to get your communications right first time, Outstanding Business English sets the scene for describing the benefits of good Business English, ideal for multinational companies where communication is a priority. For intermediate to advanced English speakers, it focuses on the areas that are easy to get wrong. This book draws on the author's wealth of experience, using real-life international business scenarios to develop your skills and provide you with some answers that even your boss might not know. You will learn a system to help you quickly and easily write emails, letters, CVs, social media communications and more.Featuring sections on punctuation and grammar, checklists to help you assess how you are getting on before moving on to the next stage and with a chapter dedicated to how to write effectively for social media, Outstanding Business English has been praised by both native and non-native writers of English as an indispensable resource.""""English is illogical, eccentric and complicated by baffling etiquette. This brilliant guide for non-native speakers decodes the world's lingua franca and makes essential reading if you form part of an international team.""""Ben Walker, editor at DialogueReview.com"""